Chemical comparison of dried rehmannia root and prepared rehmannia root by UPLC-TOF MS and HPLC-ELSD with multivariate statistical analysis - Qiande Liang; Jing Ma; Zengchun Ma; Yuguang Wang; Hongling Tan; Chengrong Xiao; Ming Liu; Beibei Lu; Boli Zhang; Yue Gao (Elsevier, 2013)
To identify the chemical differences which lead to the different therapeutic effects of dried rehmannia root (DRR) and prepared rehmannia root (PRR), we compared the chemical composition of decoctions of randomly purchased DRR and PRR using ultra performance liquid chromatography (UPLC) coupled with time-of-flight mass spectrometry and high performance liquid chromatography (HPLC) coupled with evaporative light scattering detection (ELSD) with the aid of multivariate statistical analysis. Both approaches clearly revealed compositional and quantitative differences between DRR and PRR. UPLC-MS data indicated stachyose, rehmaionoside A (or rehmaionoside B), acteoside (or forsythiaside, or isoacteoside), 6-O-coumaroylajugol (or 6-O-E-feruloylajugol, or 6-O-Z-feruloylajugol) as important discriminators between DRR and PRR decoctions. HPLC-ELSD analysis showed that the content of fructose in the decoctions of PRR was about four times greater than that of DRR (P<10−5), while sucrose content in the decoctions of PRR was only about one seventh of that in DRR (P<0.01). Our results suggest that some compounds, such as fructose, stachyose and rehmaionoside, may be responsible for the differing therapeutic effects of DRR and PRR. Furthermore, improvements in quality control for PRR, which is currently lacking in the Chinese Pharmacopoeia, are recommended.